Sleight of hand : a novel of suspense - Margolin, Phillip (HarperCollins, 2013)
While on the trail of a stolen relic, P.I. Dana Cutler is called back to Virginia where she must stop Charles Benedict, a criminal defense lawyer, amateur illusionist and professional hit man, from framing a millionaire for the murder of his much younger wife.